AB0545 GASTROINTESTINAL INVOLVEMENT IN SYSTEMIC SCLEROSIS. (2nd June 2020) - Argibay, A.; Novo, I.; Ávila, M.; Diéguez González, P.; Estévez Gil, M.; Maure, B.; Gimena, B.; Vázquez Triñanes, C.; Rivera Gallego, A.
Abstract : Background: Systemic sclerosis (SSc) is a chronic, connective tissue disease with an autoimmune pattern characterized by inflammation, fibrosis and microcirculation changes leading to internal organs malfunctions. The gastrointestinal tract (GIT) is affected in up to 90% of patients with SSc. Any part of the GIT from the mouth to the anus can be affected. There are few descriptive studies about SSc-related GIT involvement. Objectives: We aimed to characterize the GIT involvement in patients with SSc. Methods: This retrospective study included all patients from SSc cohort of our autoimmune diseases unit in a tertiary referral centre. All patients fulfilled SSc criteria proposed by the American College of Rheumatology. All subjects' histories were evaluated. Laboratory and imaging results were obtained from the hospital files. Patients with digestive manifestations were compared with patients without GIT involvement. Chi2 and t-student were used, using the statistical package SPSS25.0. Results: 83 subjects with SSc were included, 68 (81, 9%) of them were women. The mean age at the onset of SSc was 62, 1 ± 15, 3 years (range 26-89) with a mean follow-up of 9, 6 ± 7, 4 years. 80, 7% of patients had limited SSc, 12% diffuse SSc, 4.8% SSc sine scleroderma and 2, 4% early SSc. Considering the immunological profile 12 (14, 5%) had Scl70 antibodies, 49 (59%) anticentromere and 21 (25, 3%) had ANA antibodies without specificity for anti-Scl70 or anticentromere. 37, 3% patients had lung involvement, 20, 5% scleroderma and 30, 1% digital ulcers. 79, 5% of SSc patients were treated with proton pump inhibitors or H2 blockers. 53 (63, 9%) patients with SSc had GIT involvement. In 11 patients (20, 7%) digestive involvement was diagnosed before SSc (mean 26, 2 months). Esophageal involvement occurred in 83%, gastric involvement in 28, 3%, intestine involvement in 24, 5% and liver and biliary tree involvement in 26, 4%. See table 1 . No significant differences in age, sex, SSc subtype, autoantibody profile, lung involvement, skin disease, mortality and therapy were observed between patients with or without GIT manifestations. There were no deaths associated with GIT involvement. The most common pharmacologic therapy used was proton pump inhibitors (86, 8%), domperidone (20, 8%) and antibiotic rotation (17%). Conclusion: Almost two thirds of our cohort of SSc have symptomatic gastrointestinal disease. GIT manifestations are heterogeneous. Symptoms are non-specific and overlapping for a particular anatomical site. Esophagus is the most commonly affected. More than seventy-five per cent of patients experience symptoms of gastroesophageal reflux. We did not find differences among patients with and without SSc GIT disease. 17% of patients had a Reynold's syndrome. References: [1]Alastal Y et al. Gastrointestinal manifestations associated with systemic sclerosis: results from the nationwide inpatient simple. Ann Gastroenterol 2017; 30 (5): 1-6. [2]Savarino E et al. Gastrointestinal motility disorder assessment in systemic sclerosis. Rheumatology. 2013; 52(6):1095–100. [3]Steen VD et al. Severe organ involvement in systemic sclerosis with diffuse scleroderma. Arthritis and rheumatism. 2000; 43(11):2437–44. Disclosure of Interests: None declared